Clinical and laboratory effects of exchange transfusion in pediatric acute lymphoblastic leukemia with hyperleukocytosis - Lazuwardi, Rasya Azka; Andarsini, Mia Ratwita; Hernaningsih, Yetti (Paediatrica Indonesiana, 2023)
Background Acute lymphoblastic leukemia (ALL) is the most common childhood cancer. Emergency complications such as hyperleukocytosis can arise as the disease develops. Exchange transfusion is one of many cytoreductive modalities to resolve the condition. Objective To analyze the clinical and laboratory effects of exchange transfusion in childhood acute lymphoblastic leukemia patients with hyperleukocytosis. Methods This analytical retrospective cohort study with a pre- and post-test design used secondary medical record data. The obtained characteristics were the incidences of dyspnea, tachypnea, headache, intracranial bleeding, hepatomegaly, splenomegaly, lymphadenopathy, abdominal pain, fever, pallor, nausea/vomiting, and skin or mucosal bleeding; hemoglobin, white blood cell, and platelet counts; and serum potassium, sodium, calcium, phosphate, blood urea nitrogen, and creatinine levels. Results A total of 16 patients underwent exchange transfusion; they had significant reductions of the incidence of dyspnea, tachypnea, hepatomegaly, and pallor and significant improvement in the form of elevation of hemoglobin level and decrease in white blood cell counts (P<0.05 for all) compared to pre-treatment. The remainder of the variables were not significantly different between pre- and post-treatment, but a general decrease in all clinical manifestations except intracranial bleeding was observed. Conclusion Exchange transfusion has the beneficial effect of resolving hyperleukocytosis and its manifestations, although correction in laboratory outcomes that remained abnormal are still needed.